Transgenic Crops for Biofortification - Malik, Kauser Abdulla; Maqbool, Asma (Frontiers in Sustainable Food Systems, 2020)
Global Food Security concerns impact greatly on the United Nation’s Sustainable Development Goals (SDGs) which are heavily focused on removing hunger by 2030. The Global Food Security Index (GFSI) of 2017 has reported a reduction in global food security over the past year, after four years of consecutive food security gains. This has been mainly due to forced migration, climate change and political instability in many of the countries. Since nutrition is one of the main factors in maintaining a healthy lifestyle and meeting requirements of food security, several national nutrition surveys conducted in various countries have provided an avenue for governments to assess malnutrition problems across population. For example, the National Nutrition Survey carried out in 2011 and 2018 in Pakistan indicated around 50% of the population to be food insecure based on the nutritional status of available food. This survey also highlighted the acute deficiency of micronutrients in the diet resulting in several disorders, especially among the female population. In view of these facts, efforts are being made globally to enhance the nutritional value of our agricultural products especially staple crops by using several biotechnological approaches. Biofortification of crops is generally referred to as their products with enhanced nutritional value. This can be achieved either by using conventional selective breeding or through genetic engineering. Biofortification differs from fortification because it focuses to make plant foods naturally more nutritive rather than adding nutrient supplements to the foods during food processing.